From business process modeling to data model : a systematic approach - Cruz, Estrela Ferreira (2012)
Business process modeling and management approaches are increasingly used and disclosed between organizations as a means of optimizing and streamlining the business activities. Among the various existing modeling languages, we stress the Business Process Model and Notation (BPMN), currently in version 2.0. BPMN is a widespread OMG standard that is actually used either in academia and in organizations. BPMN enables business process modeling, but does not facilitate the modeling of the information infrastructure involved in the process. However, interest in the data and its preservation has increased in BPMN’s most recent version. The aim of this paper is to study BPMN 2.0, particularly on the usage and persistence of data, and present an approach for obtaining an early data model from the business process modeling, which may then be used as a starting data model in the software development process.